(untitled) (Philologia, 2021)
There is extensive bibliography devoted to the topic of modality (Coates 1983; Palmer 1990; Kärkkäinen 2003 among others), including the study of modal adverbs illustrated by more recent studies such as Hoye (1997) or Downing (2002). The majority of these studies feature a synchronic rather than diachronic approach. To fill that gap, the current paper analyses the evolution of certainly from the 19th century to present-day English. The results presented in this study are but a preliminary stage of a more extensive project currently being carried out at the Universidad Complutense de Madrid. As the analysis will show, there has been a progressive specialization of certainly, its use having more of an intra-clausal than a discursive value, save for conversational agreement, i.e. agreement with a previous turn.